Gemcitabine Plus Cisplatin Versus Non-Gemcitabine and Cisplatin Regimens as Neoadjuvant Treatment for Cholangiocarcinoma Patients Prior to Liver Transplantation: An Institution Experience - Abdelrahim, Maen; Esmail, Abdullah; Xu, Jiaqiong; Umoru, Godsfavour; Al-Rawi, Hadeel; Saharia, Ashish; Abudayyeh, Ala; Victor, David; McMillan, Robert; Kodali, Sudha; Ghobrial, Rafik M. (Frontiers in Oncology, 2022)
Background: Cholangiocarcinoma management is constantly being updated in view of existing evidence in order to establish practice guidelines and consensus statements. However, the available treatment guidelines to optimize outcomes for cholangiocarcinoma patients who require liver transplantation are still controversial. Methods: In this retrospective study, patients with locally advanced, unresectable, hilar, or intrahepatic cholangiocarcinoma with no evidence of extrahepatic disease or vascular involvement were treated with either the combination of neo-adjuvant Gemcitabine plus Cisplatin with no radiation or other standard options of neo-adjuvant treatment. Results: Out of a total of 707 liver transplant recipients were screened, 37 patients were confirmed with a diagnosis of cholangiocarcinoma and only 18 patients (11 males and 7 female) with median age of 61.83 [interquartile range: 58.27-68.74] met inclusion criteria. Of the 18 patients enrolled, 10 received Gemcitabine/Cisplatin, while 8 patients received either Gemcitabine monotherapy or Capecitabine or FOLFIRI. Days for recurrence after transplantation was 603 (IRQ: 603-603) in the Gemcitabine/Cisplatin group and 285 (267-374) days in the non-Gemcitabine/ Cisplatin group (p-value=0.18). Median days of follow-up in the Gemcitabine/Cisplatin group was 851 (813-967) days versus 1204 (618-1687) days in the non-Gemcitabine/ Cisplatin group (p-value=0.33). In non-Gemcitabine/ Cisplatin patients, overall survival was 75% (95% CI 31-93%) at both years 1 and 2; 63% (95% CI 23-86%) at years 3 to 5. In Gemcitabine/ Cisplatin patients, overall survival was 100% (95% CI 100-100%) at both years 1 and 2; 75% (95% CI 13-96%) at years 3 to 5. Three non-Gemcitabine/ Cisplatin patients died at 328 days, 340 days, and 896 days, respectively. One Gemcitabine/ Cisplatin patient died at 885 days. Conclusion: Our findings suggest improved overall survival outcomes with Gemcitabine plus Cisplatin as neo-adjuvant treatment with no concomitant radiation compared to non-Gemcitabine/ Cisplatin regimens in patients with cholangiocarcinoma prior to liver transplantation.